2015
DOI: 10.1017/s0007114515000173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a protein-free diet in the development of food allergy and oral tolerance in BALB/c mice

Abstract: The aim of the present study was to investigate the effect of a protein-free diet in the induction of food allergy and oral tolerance in BALB/c mice. The experimental model used was mice that were fed, since weaning up to adulthood, a balanced diet in which all dietary proteins were replaced by amino acid diet (Aa). The absence of dietary proteins did not prevent the development of food allergy to ovalbumin (OVA) in these mice. However, Aa-fed mice produced lower levels of IgE, secretory IgA and cytokines. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Consumption of AA diet was nutritionally equivalent to CAS diet concerning parameters such as weight maintenance and levels of total serum proteins, albumin, transferrin, glycemia, and triglycerides. Previous studies in humans and animals also showed nutritional equivalence between diets containing intact proteins and free amino acids ( 8 , 11 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Consumption of AA diet was nutritionally equivalent to CAS diet concerning parameters such as weight maintenance and levels of total serum proteins, albumin, transferrin, glycemia, and triglycerides. Previous studies in humans and animals also showed nutritional equivalence between diets containing intact proteins and free amino acids ( 8 , 11 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 77%
“…The immunological role of dietary proteins has been already addressed by studies using either a standard rodent diet in which intact proteins were replaced by equivalent amounts of amino acids ( 7 , 11 ) or by elemental diets ( 8 , 28 ). Menezes et al ( 7 ) showed that exposure to food proteins after weaning plays a physiological role in inducing the maturation of the immune system both locally and systemically ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To induce food allergy, Mice (n=5 per group, a total of 15 mice in three OVA challenged groups) were intraperitoneally (i.p.) injected with 50 µg OVA (Grade V; A-5503; Sigma-Aldrich; Merck KGaA) in 1 mg alum adjuvant on days 0 and 14 as previously described ( 38 ). From day 28, the mice were challenged intragastrically with 50 mg of OVA in 250 µl PBS every other day for 12 days (6 administrations).…”
Section: Methodsmentioning
confidence: 99%